Qualidade de melão Cantaloupe cultivado sob diferentes controles de alcalinidade e adubação fosfatada - Costa, Eleonora Barbosa Santiago da (2018)
The culture of melon has stood out as one of the main fruits in volume of world production, being among the most exported horticultural products of Brazil. However, Chapada do Apodi soils, used in irrigated agriculture, are of calcareous origin as well as irrigation water, conditions that cause soil alkalinity throughout crops and affect the productivity and quality of crops, as the mineral absorption by the plant occurs in optimal pH range. Thus, this work aims to evaluate the effects of soil management by correcting soil alkalinity and analyzing the use of phosphate fertilization in post-harvest quality characteristics. For this, two experiments were carried out, one with Cantaloupe 'Hy-mark' melon and the other with Cantaloupe 'Florentino' melon. The experiments were carried out in Cumaru Farm, in the municipality of Upanema-RN, with a randomized block design in subdivided 3x4 plots with four replications; (0, 50, 100, 150 kg ha-1), with two acidifying products (sulfur and sulfuric acid) and without acidifying agent (without pH correction) and subplots with four phosphorus doses. The fruits were transported to the UFERSA Food Laboratory, where they were evaluated for longitudinal and transverse diameter, peel thickness, pulp firmness, soluble solids (SS), titratable acidity (TA), pH, vitamin C, total soluble sugars (AS), SS / AT ratio and total phenols (FT) and carotenoids (CA). The data were submitted to analysis of variance. For qualitative variables, the means were compared by the Tukey test at 5% of probability; for the quantitative variables, the regression analysis was performed using the software Sisvar, v. 5.3. In the experiment with Cantaloupe 'Hy-mark', there was an effect of the factors studied on the FT content of the fruits. The increase in the P2O5 doses resulted in an increase in the AS and the longitudinal and transverse diameters of the fruits. Sulfur treatment increased the SS / AT and vitamin C ratio of the pulp. The treatment with sulfuric acid resulted in a higher SS content. The sulfur treatment influenced the TA positively and the increase of phosphorus doses decreased the TA of the fruits. For the other parameters, no effect of the treatments was observed. In the experiment with Cantaloupe 'Florentino', the acidifiers contributed to the higher firmness values of the fruits pulp, the elemental sulfur provided better vitamin C contents and reduced fruit pH. However, the use of elemental sulfur in conjunction with phosphorus doses contributed positively to the decrease in titratable acidity and increased SS / AT ratio. Phosphorus doses affected the pH, which increased linearly, thus verifying less acidic fruits